Truncus arteriosus with meandering pulmonary arteries: Atypical truncus arteriosus - Oteyaka , Emre; Kuguoglu , Okan Eren; Sari , Gizem; Basunlu , Mehmet Turan; Yozgat , Yilmaz; Ugurlucan , Murat; Turkoglu , Halil (Journal of Surgery and Medicine, 2023)
Truncus arteriosus is a rare, cyanotic, and congenital heart defect occurring due to failure in the differentiation of the aorta and the pulmonary artery during fetal development. The disease is categorized into four sub-categories in the Van Praagh and Collett & Edwards classification systems according to the origin of the pulmonary arteries. Surgical correction of the pulmonary arteries and repair of the ventricular septal defect is the preferred treatment strategy of choice; this intervention is required early in life. Here, we report a four-month-old baby with truncus arteriosus consisting of atypical pulmonary anatomy undefined by either the Van Praagh or the Collett & Edwards classification systems who underwent successful corrective surgery.